Encyclopedia of the Sciences of Learning 2012
DOI: 10.1007/978-1-4419-1428-6_653
|View full text |Cite
|
Sign up to set email alerts
|

Scaffolding Discovery Learning Spaces

Abstract: Discovery learning spaces may be created in online learning environments to encourage learner-directed training and learning. Such "autodidaxy" learning tends to be autonomous and learner-directed. This chapter addresses the importance of learner empowerment through the building of learner orientation, decision supports, community supports, and new learning archival. This also advocates promotion of learner selfefficacy and decision-making. The Web-based design of online discovery spaces needs to be aligned in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 5 publications
1
5
0
1
Order By: Relevance
“…By using discovery learning model, students are involved directly in learning the problems, to find the answer through searching and discovering the problem. This research is in tune with the opinion of Zydney et al, (2012) that stated discovery learning model gives room for students to learn in making decision and to make new competency.…”
Section: Resultssupporting
confidence: 68%
“…By using discovery learning model, students are involved directly in learning the problems, to find the answer through searching and discovering the problem. This research is in tune with the opinion of Zydney et al, (2012) that stated discovery learning model gives room for students to learn in making decision and to make new competency.…”
Section: Resultssupporting
confidence: 68%
“…This process made students develop a deeper understanding of grammar rules. The corrective feedback was done in this study in order to avoid inaccuracy suggested by Kirschner et al (2006) or misconception (Hai-Jew, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, as elaborated previously, the way to motivate the students in writing is by applying TPS and TCF within discovery learning strategy. The learning task or activity is seen in the form of scaffolding discovery (Hai-Jew, 2008) which enables them to produce their own sentences accurately. It is in line with the concept of input hypothesis by Krashen (1985); Krashen (1994); Krashen (2003) which stated that the input should be 1 +1 and with the output hypothesis as well stated by Swain (1985); Swain and Lapkin (1995) and Ellis (1991) who stated that when a learner uttered or produced wrong expressions or sentences, s/he could also find relevant input.…”
Section: Discussionmentioning
confidence: 99%
“…Motivation also influences this independence; motivation is essential in completing learning activities (Geng et al, 2019). If motivation is not disturbed, memory, cognition, intelligence, and reasoning will run well (Hai-Jew, 2012;Sangsawang, 2020). Good cognition makes learners act consciously of their own accord, plan their learning activities, and do practice questions even though the teacher has not assigned the task.…”
Section: Indicatormentioning
confidence: 99%